Upaya Meningkatkan Motorik Halus Melalui Origami pada Anak Usia Dini di TK Al-Hikmah - Asmidar Parapat (AUD Cendekia, 2021)
This study aims to improve fine motor skills through origami in  early  childhood  at  Al-Hikmah  Kindergarten.  The  research  method  used was  collaborative  classroom  action  research  using  the  model  of  Kemmis and  Mc  Taggart.  The  subjects  of  the  study  were  24  children  of  Group  A consisting  of  10  boys  and  14  girls.  The  object  of  this  research  is  fine  motorskills. Data collection methods used were observation, documentation, and interviews. The   instruments   used   were   observation   guidelines   and interview    guidelines.    The    data    were    analyzed    using    descriptive quantitative and qualitative techniques. The success indicator determined is if  at  least  75%  of  the  19  children  have  fine  motor  skills  with  good  criteria. This  research  was  conducted  in  three  cycles.  The  results  showed  that  the children's fine  motor skills improved after the action through origami. The steps  taken  to  improve  children's  fine  motor  skills  are  1)  the  teacher explains how to fold paper using the demonstration method; 2) the child is given reinforcement with the word "folds of the heart" that has been made;3) children are given rewards in the form of praise and souvenirs; 4) use of motive folding paper to attract children's interest